Changes in hemodynamic parameters of the tongue in persons with glossodynia as a result of treatment (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
Patient complaints of a burning sensation in the mouth represent one of the most difficult challenges for dental professionals. This condition is further aggravated if it is accompanied by pain. Pain is a common cause of suffering and seriously impairs a person's quality of life. The International Association for the Study of Pain (IASP) defines this condition as “burning pain in the tongue... associated with normal findings and laboratory findings, lasting at least 4–6 months” [4].